Utility-scale renewable energy job creation : an investigation of the South African Renewable Energy Independent Power Producer Procurement Programme (REIPPPP) - Stands, Sarah Reed (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2015.